2019
DOI: 10.1111/psyg.12422
|View full text |Cite
|
Sign up to set email alerts
|

What influences self‐perceived competence and confidence in dementia care home staff? A systematic review

Abstract: Background Dementia care staff working in long‐term care settings are often exposed to a variety of complex situations that can be emotionally challenging, and a lack of adequate support and limited training opportunities may contribute to high levels of staff turnover in this area. Good‐quality training may be beneficial for improving the quality of care provided, and in improving staff confidence and morale. This systematic review aimed to establish how dementia care home staff perceived their own competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Little attention being given to nursing staff and their BPSD care competence has resulted in the insufficient and inconsistent content of relevant education, undermining the quality of BPSD care [ 17 , 18 ]. Continuing BPSD education that has a clear basis on competencies and specifically targets nursing staff would generate consistent positive outcomes for practice and residents in LTCFs [ 19 , 20 ]. Therefore, it is imperative to establish an educational direction suitable for BPSD care in LTCFs that aims to improve the nursing staff’s competence in providing direct care.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention being given to nursing staff and their BPSD care competence has resulted in the insufficient and inconsistent content of relevant education, undermining the quality of BPSD care [ 17 , 18 ]. Continuing BPSD education that has a clear basis on competencies and specifically targets nursing staff would generate consistent positive outcomes for practice and residents in LTCFs [ 19 , 20 ]. Therefore, it is imperative to establish an educational direction suitable for BPSD care in LTCFs that aims to improve the nursing staff’s competence in providing direct care.…”
Section: Introductionmentioning
confidence: 99%
“…LGBT+ community (Jurček et al, 2020). Additional outcomes included improved comfort (Higgins et al, 2019), confidence, competence (Higgins et al, 2019;Rivett et al, 2019;Surr et al, 2017) and self-ef ficacy in delivering care (Pleasant et al, 2020;Surr et al, 2017). For informal carers, caregiver burden was also assessed (Pleasant et al, 2020).…”
Section: Measures Used When Monitoring the Effectiveness Of Learningmentioning
confidence: 99%
“…Specific skills included supporting activities of daily living though improved management of behavioural symptoms (Bauer et al, 2018), understanding the nature of dementia (Rivett et al, 2019;Spector et al, 2013), behaviour management skills (Kuske et al, 2007) and communication skills (Eggenberger et al, 2013;Nguyen et al, 2019).…”
Section: Contentmentioning
confidence: 99%
“…Care home staff often provide care for residents with complex needs as a result of a variety of conditions, including dementia. The nature of dementia care can be demanding of their knowledge and skills and also emotionally challenging [90]. Rivett and colleagues [90] also identified that a lack of adequate support and limited training opportunities for care home staff may contribute to high levels of staff turnover in this area.…”
Section: Confidence and Competence To Carementioning
confidence: 99%
“…The nature of dementia care can be demanding of their knowledge and skills and also emotionally challenging [90]. Rivett and colleagues [90] also identified that a lack of adequate support and limited training opportunities for care home staff may contribute to high levels of staff turnover in this area. However, Goodman et al [89] identified that when a care home resident is approaching their end-of-life there is often uncertainty about the roles and responsibilities of the care home staff, the families and primary care professionals.…”
Section: Confidence and Competence To Carementioning
confidence: 99%